On Creativity: From conceptual ideas towards a systemic understanding - Lech Suwala (European Colloquium on Culture, Creativity and Economy (CCE) Working Paper Compendium, 2017)
The `creativity hype' has nurtured both manifold insights by dint of academic studies, research reports and policy papers as well as an array of extensive shortcomings concerning the academic understanding of `creativity'. In the realm of economic geography, an inflationary and unwitting utilization of the term `creativity' in general, and creativity in arts and sciences in particular has prevented a serious debate and revealed four main deficiencies about: (1) the nature of creativity, (2) the process of creativity, (3) allocation of meaning (to) creativity as well as (4) the general relationship between creativity and space. This conceptual paper contributes to shed some light upon these shortcomings by assembling, juxtaposing and systemizing interdisciplinary perspectives, insights and findings on these specific types of creativity. The results illustrate that creativity (in general) is characterized by something with meaningful novelty (originality component), which is useful and valuable at the same time (effectiveness component), verified (by individuals or teams), validated (by communities) and selected (by markets) against a frame of reference. Interestingly, despite a traditional focus on meaningful novelty (originality component) in creativity in arts and sciences, the very logic of bisociation (the sole creative act) is fundamentally different. Moreover, modern views emphasize the effectiveness component within these types of creativity as reflected in cultural and creative industries or academic entrepreneurship. Ultimately, a potpourri of manifold spatial metaphors connected to creativity can be found in literature; therefore, a systemic attempt towards the general relationship between creativity in arts and sciences and space (understood as location, place, and landscape) will be introduced.
Keywords: L26; O31; O35; O30; P25; 330; Creativity; Innovation; Entrepreneurship; Economic Geography; Space